IMPLEMENTATION OF MINIMUM WAGES ACT IN AGRICULTURAL SECTOR - et. al., Pallavi S. Pathare (International Journal of Modern Agriculture, 2021)
The Minimum Wages Act was enacted in 1948 and it is one of the oldest labour legislation enacted in India. But still today a very large segment of the workforce left outside the purview of the Act. The Minimum Wages Act is one of the most important strategies in India to improve the living conditions of the poor by giving them minimum wages. This is also helpful for the economic development of the country. Minimum Wages are not equal to all sectors, mainly; the minimum wages for the agricultural sector is not the same to be given at all the regions of the country. The same occupation with the same labour has variable minimum wages. Women mainly get less pay than men for the same work, also women get differential treatment at work and are perceived less able in work than men. There is a need for economic empowerment for women, this can reduce poverty for everyone, and this could also help in undermining gender equality because no woman in the world enjoys absolute equality with men. Everywhere women are exploited, discriminated, and face inequality. This paper examines the enactments made by the Government of India to improve minimum wages and other conditions of work at the workplace; the paper also throws light on problems faced by women working in the agricultural sector and includes opinion of experts of law on the same